Unidentified versus Identified Peer Feedback Combined with Teacher Feedback to Improve Second Language Students’ Online Writing - Amanda Pradhani Yanwar; Jirarat Sitthiworachart; John Morris; Mike Joy (Language Teaching Research Quarterly, 2026)
This study investigated the effectiveness of the combination of peer corrective feedback (PCF) and teacher feedback (TF) on students’ writing performance and proficiency with an focus on mechanics, style, organization, content, and grammar. The participants were sophomores majoring in English at a state university in Indonesia. Three groups of thirty students each were formed from the students: an unidentified PCF+TF group, an identified PCF+TF group, and a TF group. During the initial phase and at last, each group received pre- and post-tests. For two weeks, students in the unidentified and identified PCF+TF groups were involved in a two-hour in-class feedback training session. Written assignments and transcripts of interviews were used to collect data. In the argumentative essay writing post-test, the unidentified PCF+TF group performed better than the other two groups with considerably higher scores of mean (p < 0.01). Furthermore, there was a substantial increase (p < 0.05) in the post-test scores of mean for the five writing aspects (mechanics, style, organization, content, and grammar) in both the unidentified PCF+TF and identified PCF+TF groups. The whole performance of writing and proficiency substantially increased when PCF and TF were combined with feedback training. This study emphasizes how crucial it is to combine PCF and TF while teaching English in order to increase learning outcomes.
Keywords: Student Assessment and Feedback; EFL/ESL Teaching and Learning; Technology-Enhanced Education Studies